Effect of rapamycin treatment during post‐activation and/or in vitro culture on embryonic development after parthenogenesis and in vitro fertilization in pigs. (10th April 2017) - Elahi, F; Lee, H; Lee, J; Lee, ST; Park, CK; Hyun, S‐H; Lee, E
Contents: This study investigated the effects of early induction of autophagy on embryonic development in pigs. For this, oocytes or embryos were treated with an autophagy inducer, rapamycin (RP), during post‐activation (Pa), in vitro fertilization (IVF) and/or in vitro culture (IVC). When parthenogenesis (PA) embryos were untreated (control) or treated with various concentrations of RP for 4 hr during Pa, 100 nm RP showed a higher blastocyst formation (48.8 ± 2.7%) than the control (34.6 ± 3.0%). When PA embryos were treated during the first 24 hr of IVC, blastocyst formation was increased ( p < .05) by 1 and 10 nm RP (61.9 ± 3.0 and 59.6 ± 3.0%, respectively) compared to the control (43.2 ± 1.8%) and 100 nm RP (47.8 ± 3.2%), with a higher embryo cleavage in response to 10 nm RP (87.3 ± 2.4%) than the control (74.1 ± 3.2%). RP treatment during IVC and Pa + IVC showed increased blastocyst formation (44.7 ± 2.5 and 44.1 ± 2.0%, respectively) compared to the control (33.2 ± 2.0%). In addition, RP treatment during Pa and/or IVC increased glutathione content and inversely reduced reactive oxygen species. In IVF, RP treatment for 6 hr during IVF significantly increased embryonic development (34.0 ± 2.6%) compared to the control (24.8 ± 1.6%), but treatment during IVC for 24 hr with RP did not (23.0 ± 3.8%). Autophagy was significantly increased in PA oocytes by the RP treatment during Pa but not altered by the treatment during the first 24 hr of IVC. Overall, RP treatment positively regulated the pre‐implantation development of pig embryos, probably by regulating cellular redox state and stimulating autophagy.